2016
DOI: 10.1007/s12035-016-9996-x
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia

Abstract: Although monozygotic (MZ) twins have theoretically identical nuclear DNA sequences, there may be phenotypic differences between them caused by somatic mutations and epigenetic changes affecting each genome. In this study, we collected eight families of MZ twins discordant for schizophrenia with the aim of investigating the potential role of mitochondrial DNA (mtDNA) heteroplasmy in causing the phenotypic differences between the twin pairs. Next-generation sequencing (NGS) technology was used to screen the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…They observed from one to four point heteroplasmies (i.e., the presence of more than one mtDNA type in an individual due to mutations) in all ten sets of twins, demonstrating the efficiency of ultradeep mtGenome in differentiating identical twins. Opposing results were observed by Li et al: However, no heteroplasmy differences were observed in the analysis of eight pairs of MZ twins (Li et al, 2017). They suggested that Wang's data contained many potential errors.…”
Section: Identification Of Monozygotic Twinsmentioning
confidence: 76%
“…They observed from one to four point heteroplasmies (i.e., the presence of more than one mtDNA type in an individual due to mutations) in all ten sets of twins, demonstrating the efficiency of ultradeep mtGenome in differentiating identical twins. Opposing results were observed by Li et al: However, no heteroplasmy differences were observed in the analysis of eight pairs of MZ twins (Li et al, 2017). They suggested that Wang's data contained many potential errors.…”
Section: Identification Of Monozygotic Twinsmentioning
confidence: 76%
“…Discordant phenotypes of MZ twins are common and widely discussed in genetic studies (van Dongen et al, 2012; Zwijnenburg et al, 2010), and mtDNA heteroplasmy is believed to involve in the difference of phenotypes (Detjen et al, 2007; Li et al, 2016). To examine whether mtDNA composition contributes to this pedigree, we also compared mtDNA composition in the maternal lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is implicated in several human diseases, including cancer ( 41 ), diabetes ( 42 ), cardiovascular disease (CVD) ( 43 ), HIV/AIDS ( 44 ), multiple sclerosis ( 45 ), Alzheimer’s, Parkinson’s, Huntington’s ( 34 ), autism ( 46 ), and schizophrenia ( 47 ). Mitochondria are also implicated as drivers of aging phenotypes ( 1 , 20 ).…”
Section: The Mitochondria In Aging and Complex Diseasementioning
confidence: 99%